Social Support and Anxiety Levels of Pregnant Women During The COVID-19 Pandemic - Santi, Mina; Dewi, Cici Nur Treviana; Purnamaningrum, Yuliasti Eka (Window of Health : Jurnal Kesehatan, 2023)
The COVID-19 pandemic was a global health emergency that caused anxiety, including for pregnant women. In Ireland, clinical anxiety for pregnant women during the Covid-19 pandemic reached 63.4-66.7%. Anxiety in pregnant women increases the hormone cortisol, which suppresses the immune system and increases blood sugar levels, resulting in low birth weight (LBW) babies and delayed fetal growth. Social support influences anxiety in pregnant women. The research aims to determine the relationship between social support and anxiety among pregnant women during the COVID-19 pandemic. The research method is a quantitative survey with a cross-sectional approach. Using a purposive sampling technique, the sample was 397 pregnant women in the Special Region of Yogyakarta Province. Data were collected using the Corona Anxiety Scale questionnaire and social support questionnaire. Data analysis used the Somer's d Gamma test. The results show that the majority of respondents live in Kulonprogo Regency (35.5%), graduated from high school/vocational school (53.7%), do not work (51.9%), family income is the Provincial Minimum Wage and above (70 .3%) and primigravida (63%). Mothers with low social support experienced more anxiety (66.7%). Variables related to anxiety in pregnant women are employment (p-value= 0.024), family income (p-value= 0.023), parity (p-value= 0.024), and social support (p-value= 0.023). The unrelated variable is education (p-value= 0.693). There is a relationship between social support and anxiety among pregnant women during the COVID-19 pandemic. Anxiety is more experienced in pregnant women with low social support. Community health centers as primary healthcare facilities should facilitate access to mental health services by developing clinical teleconsultation and increasing public knowledge about the importance of social support to prevent anxiety.